If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(3k + -7) = 196 Reorder the terms: -7(-7 + 3k) = 196 (-7 * -7 + 3k * -7) = 196 (49 + -21k) = 196 Solving 49 + -21k = 196 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-49' to each side of the equation. 49 + -49 + -21k = 196 + -49 Combine like terms: 49 + -49 = 0 0 + -21k = 196 + -49 -21k = 196 + -49 Combine like terms: 196 + -49 = 147 -21k = 147 Divide each side by '-21'. k = -7 Simplifying k = -7
| -9(8x-35)=-477 | | 368=r+8(5+5r) | | -2y+6x=12 | | 6w-2=28 | | 8-5(3+8a)=-327 | | 2[a-5]=14 | | 3=9-2c | | 3tg^4x-10tg^2x+3=0 | | 4x+32-2x+16=2 | | 12[3+a]=48 | | 7-6(8x+2)=-293 | | y+11=5y+29 | | 0.5(3x-1)+0.5x=2x-0.5 | | 12[x+11]=156 | | x-0.1=0.9 | | 4.8x-8.6=20.2 | | 5(4b+3)=135 | | (12)=-3x+10 | | 1485=-11(9x+9) | | 14x-8x=42 | | -15=.5[x+6] | | 5(5p+4)+4(3p+2)= | | 2n+25=4n+23 | | 190/50 | | 7w+2w=45 | | y-10=-x+2 | | x-3.6=1.4 | | 5k-4=2k+11 | | -5+8k=7k+4-7 | | Ab/c=xy/z | | 3x(2xy)(-3x^5y^2)= | | 15/6xt=81 |